Effects of household vectors on child health and its determinants in southwest, Ethiopia correspondence analysis - Alemayehu, Bezuayehu; Mekonnen, Besufekad; Addisu, Abebaw; Asres, Abyot (Frontiers in Public Health, 2024)
Background: Household vectors transmit pathogens from one child to another. This study aimed to investigate the prevalence and determinants of household vectors on child health.Methods: A community-based cross-sectional study design was conducted, during which a total of 846 household data were collected using a pretested questionnaire and simple random sampling technique. The data was entered into EpiData3.4 and then exported to Stata 14 software for analysis. A multivariable logistic regression analysis was conducted to identify significant factors associated with household vectors that contribute child health problems.The correspondence analysis was used to determine statistically significant effects or associations between household vectors and child health problems, that was explained by the percentage of variance.Results: This study revealed that the prevalence of household vector effects among children was 35.5% suchas itching, allergies, nuisances and aesthetically displeasing factors. Households with no formal education were significantly 36% less likely to be affected compared to their counterparts (AOR 0.64, 95% CI 0.41, 0.99). Housewives are significantly 2.21 times more likely to be bexposed to household vectors compared to government workers (AOR 2.21, 95% CI 1.23, 3.70). Caregivers who had limited awareness of household vectors were 98.6% less likely to be affected compared to their counterparts (AOR 0.014; 95% CI 0.01-0.04). Similarly, children from households that consumed less than 20 liters of water per individual were 1.45 times more likely to be at risk compared to children from households that consumed more water (AOR 1.45, 95% CI 1.02, 2.07). The infestations of household vectors were found to be statistically significant and were associated with the occurrence of child health problems. This significant association accounted for 86.8 percent of the explained variance.Addressing the high burden of household vectors on child health requires interventions that target informal education, limited access to information, and inadequate access to safe water. Implementing effective vector control measures is crucial to reduce the incidence of vector-borne diseases among children.